Fracture zones in the Mid Atlantic Ridge lead to alterations in prokaryotic and viral parameters in deep-water masses - Muck, Simone; Griessler, Thomas; Köstner, Nicole; Klimiuk, Adam; Winter, Christian; Herndl, Gerhard J. (Frontiers in Microbiology, 2014)
We hypothesized that mixing zones of deep-water masses act as ecotones leading to alterations in microbial diversity and activity due to changes in the biogeochemical characteristics of these boundary systems. We determined the changes in prokaryotic and viral abundance and production in the Vema Fracture Zone (VFZ) of the subtropical North Atlantic Ocean, where North Atlantic Deep Water (NADW) and Antarctic Bottom Water (AABW) are funneled through this narrow canyon and therefore, are subjected to intense vertical mixing. Consequently, salinity, potential temperature, oxygen, PO4, SiO4, NO3 were altered in the NADW inside the VFZ as compared to the NADW outside of the VFZ. Also, viral abundance, lytic viral production and the virus-to-prokaryote ratio were elevated in the NADW in the VFZ as compared to the NADW outside the VFZ. In contrast to lytic viral production, lysogenic VP and both the frequency of lytically (FIC) and lysogenically infected cells (FLC) did not significantly differ between in- and outside the VFZ. Generally, FIC was higher than FLC throughout the water column. Prokaryotic (determined by T-RFLP) and viral (determined by RAPD-PCR) community composition was depth-stratified inside and outside the VFZ. The viral community was more modified both with depth and over distance inside the VFZ as compared to the northern section and to the prokaryotic communities. However, no clusters of prokaryotic and viral communities characteristic for the VFZ were identified. Based on our observations, we conclude that turbulent mixing of the deep water masses impacts not only the physico-chemical parameters of the mixing zone but also the interaction between viruses and prokaryotes due to a stimulation of the overall activity. However, only minor effects of deep water mixing were observed on the community composition of the dominant prokaryotes and viruses.